Development of a library transformation roadmap. - Lee, Yoke Peng. (2013)
Change and response to change are inevitable in libraries in this fast changing era of the global competitive knowledge economy. Transformation begins when a library finds that it can no longer continue functioning as it was. Transformation is a significant process of radical change for libraries that recognize that they need drastic change in every dimension of their business activities, and overhaul the organisational structure with a new mission and vision for the future. A library transformation roadmap is a detailed plan that helps the libraries identify what should be done, improved and measured. It is a strategy and action plan, with set goals and long term solutions for the challenges and opportunities that lie ahead. Unfortunately, there is a lack of library literature paying attention to library organization transformation plan and framework that can guide libraries. The objective of this study is to develop a framework for developing a transformation roadmap for a library, taking into consideration the social, cultural and economic context of the library. It is useful for libraries to use a structured framework and methodology as a step-by-step guide when they develop the library transformation roadmap.